2020
DOI: 10.1007/s12369-020-00679-0
|View full text |Cite
|
Sign up to set email alerts
|

Socially Assistive Robots as Mental Health Interventions for Children: A Scoping Review

Abstract: This is a repository copy of Socially assistive robots as mental health interventions for children : a scoping review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 68 publications
(121 reference statements)
1
39
0
Order By: Relevance
“…A study of the use of the Sony Aibo robot dog in a residential care home found a positive impact on the experience of loneliness similar to that generated by interaction with a real dog ( Banks et al., 2008 ). Recent work on social robots as interventions for mental health also indicates the potential for the affective components of human-robot interaction to generate emotional comfort and to scaffold feelings of self-worth ( Ostrowski et al., 2019 ; Kabacińska et al., 2020 ). The effectiveness of robots as social companions can also be improved by adapting their cognitive architectures and capabilities to suit specific populations, such as people living with dementia ( Perugia et al., 2020 ).…”
Section: Potential Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of the use of the Sony Aibo robot dog in a residential care home found a positive impact on the experience of loneliness similar to that generated by interaction with a real dog ( Banks et al., 2008 ). Recent work on social robots as interventions for mental health also indicates the potential for the affective components of human-robot interaction to generate emotional comfort and to scaffold feelings of self-worth ( Ostrowski et al., 2019 ; Kabacińska et al., 2020 ). The effectiveness of robots as social companions can also be improved by adapting their cognitive architectures and capabilities to suit specific populations, such as people living with dementia ( Perugia et al., 2020 ).…”
Section: Potential Benefitsmentioning
confidence: 99%
“…The interactive and dynamic features of social robots, and their ability to understand and respond to human emotion, make them candidate solutions for application domains that require social engagement and comfort. In healthcare, social robots are being investigated and implemented as tools to assist patients by means of emotional support across the lifespan, from pediatric populations ( Kabacińska et al., 2020 ) to older adults ( Broekens et al., 2009 ; Robinson et al., 2014 ; Prescott and Caleb-Solly, 2017 ; Pu et al., 2018 ; Papadopoulos et al., 2020 ). In education, social robots are being used as tutors or co-learners to promote cognitive and affective outcomes including social skills development ( Belpaeme et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sensor and device network technologies were applied in 11 studies. Apart from the multi-device systems that were used with wearable technologies ([ 14 , 39 , 44 , 61 ]), a large proportion of the solutions were distributed or multi-agent systems that were developed mainly based on a client/server architecture. The client devices could interact with each other online or offline, and their status could also reflect on the server device.…”
Section: Resultsmentioning
confidence: 99%
“…Among different kinds of Socially Assistive Systems, robotic systems include a large number of studies, such as Socially Assistive Robots for older adults ([ 29 , 30 , 38 ]) and children [ 39 ]. Some existed review papers have reported such field, so we did not include robotic systems in our systematic review.…”
Section: Methodsmentioning
confidence: 99%
“…There is growing interest in developing SAS, and every year many new studies are published. As we have not identified systematic reviews that focused on assistive technologies for support social interactions other than robotic systems ([ 21 , 22 , 23 , 24 ]), there is a need to categorize the current research studies. Hence, we have outlined the research methods used to study SASs, identify the outcomes, inform design practice, and guide further research.…”
Section: Introductionmentioning
confidence: 99%